Spectral sensing for tissue diagnosis during lung biopsy procedures: The importance of an adequate internal reference and real-time feedback. (August 2016) - Spliethoff, Jarich W.; de Boer, Lisanne L.; Meier, Mark A.J.; Prevoo, Warner; de Jong, Jeroen; Bydlon, Torre M.; Sterenborg, Henricus J.C.M.; Burgers, Jacobus A.; Hendriks, Benno H.W.; Ruers, Theodoor J.M.
Highlights: A method for biopsy guidance based on diffuse reflectance spectroscopy is presented. The method relies on intrinsic optical contrast based on tissue composition. Clinical feasibility was demonstrated during 23 routine lung biopsy procedures. The integrated fibre-optic tool provided accurate real time tissue diagnosis. Abstract: Objectives: Difficulties in obtaining a representative tissue sample are a major obstacle in timely selecting the optimal treatment for patients with lung cancer or other malignancies. Having a modality to provide needle guidance and confirm the biopsy site selection could be of great clinical benefit, especially when small masses are targeted. The objective of this study was to evaluate whether diffuse reflectance spectroscopy (DRS) at the tip of a core biopsy needle can be used for biopsy site confirmation in real time, thereby enabling optimized biopsy acquisition and improving diagnostic capability. Materials and methods: We included a total of 23 patients undergoing a routine computed tomography (CT) guided transthoracic needle biopsy of a lesion suspected for lung cancer or metastatic disease. DRS measurements were acquired during needle insertion and clinically relevant parameters were extracted from the spectral data along the needle paths. Histopathology results were compared with the DRS data at the final measurement position. Results: Analysis of the collective data acquired from all enrolled subjects showed significant differences (p < 0.01) for blood content, stO2, water content, and scattering amplitude. The identified spectral contrast matched the final pathology in 20 out of 22 clinical cases that could be used for analysis, which corresponds with an overall diagnostic performance of 91%. Three cases underlined the importance of adequate reference measurements and the need for real time diagnostic feedback. Continuous real time DRS measurements performed during a biopsy procedure in one patient provided clear information with respect to the variation in tissue and allowed identification of the tumour boundary. Conclusions: The presented technology creates a basis for the design and clinical implementation of integrated fibre-optic tools for a variety of minimal invasive applications.